Carbon nanofiber-based copper/zirconia catalyst for hydrogenation of CO2 to methanol - Din, I.U. (Elsevier Ltd, 2017)
This article describes the synthesis of methanol by the direct hydrogenation of CO2 over Cu/ZrO2 catalyst at different ZrO2 concentrations (5, 10, 15, 20 and 25 wt.) in a three-phase phase reactor. The techniques of N2 adsorption/desorption, x-ray diffraction, x-ray photoelectron spectroscopy, transmission electron microscopy, temperature-programmed desorption by CO2, N2O chemisorption and inductively coupled plasma optical emission spectrometry were employed for catalyst characterization. At a reaction temperature of 180 °C, pressure of 3.0 MP and 0.020 g/mL of the catalyst, the conversion of CO2 and the yield of methanol were 10 and 25 g/kg.h, respectively. Surface area of the metallic copper was increased from 8.1 to 9.5 m2/g with the presence of ZrO2 from 5 to 15 wt.. The methanol turnover frequency exhibited a linear relationship with ZrO2 concentration. Methanol synthesis rate was progressively increased with increasing fraction of dispersed copper. A comparative study with the literature revealed better activity of this novel catalyst at relatively low reaction conditions.